Systemic sclerosis and the risk of perioperative major adverse cardiovascular events for inpatient non‐cardiac surgery. (4th March 2019) - Luo, Yiming; Jiang, Changchuan; Krittanawong, Chayakrit; Arevalo Molina, Ana Belen; Murray, Shane; Huang, Feng; Zhang, Jianglin; Salgado, Maria; Xu, Jiehui
Abstract: Aim: We investigated the association between systemic sclerosis (SSc) and perioperative cardiovascular risk for inpatient non‐cardiac surgical procedures. Methods: We used data from the National Inpatient Sample (NIS) for the year 2014 to identify patients undergoing inpatient non‐cardiac surgery. SSc and major adverse cardiovascular events (MACE) were defined by International Classification of Diseases 9th Revision diagnosis codes. Univariate and multivariate analyses were performed. We adjusted for demographic information, socioeconomic status, cardiac comorbidities, cardiovascular risk factors and procedural category. Two models were used with different categorization strategies for surgical procedures. Results: A total of 8 156 379 hospitalizations for non‐cardiac surgeries were included, 4385 of which had a diagnosis of SSc. Patients with SSc were older, more likely to be female and Caucasian and with higher cardiac and systemic comorbidity burden. In univariate analysis, SSc was associated with higher risk of perioperative MACE (odds ratio [OR] = 2.9; P < 0.001) and all‐cause death ( P = 3.07; P < 0.001). Multivariate analysis yielded conflicting results regarding the association between SSc and perioperative MACE (Model 1: OR = 1.42; P = 0.146; Model 2: OR = 1.59; P = 0.048). Subsequent analysis showed that only perioperative myocardial infarction (Model 1 OR = 1.85; P = 0.048; Model 2 OR = 1.94; P = 0.031) was independently associated with SSc. Conclusion: We did not find consistent association between SSc and perioperative MACE in non‐cardiac surgical procedures. SSc may be associated with perioperative myocardial infarction.